2018
DOI: 10.4184/asj.2018.12.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal Spinal Ligamentum Flavum Thickening: A Magnetic Resonance Imaging Study

Abstract: Study DesignA retrospective radiological study of the ligamentum flavum (LF).PurposeWe determined the relationship of dorsal spinal LF thickening with age and sex using magnetic resonance imaging (MRI). We also determined whether LF thickening has a predominant tendency to occur at a specific dorsal level and on a specific side.Overview of LiteratureMany researchers have studied LF thickness at dorsal levels in patients with compressive myelopathy. However, there is a dearth of literature pertaining to the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…119 Maximum thickness of the ligamentum flavum in the thoracic spine is at the T10-T11 level (3.3 AE 0.9 mm), possibly due to larger tensile forces and mobility at this level. 119 In the lumbar spine, ligamentum flavum thickness > 4 mm is considered hypertrophy. 102,120 The ligamentum flavum tends to be thickest at L4-L5 followed by L5-S1 and is $ 5 to 10% thicker on the left side.…”
Section: Ligamentum Flavum Thicknessmentioning
confidence: 95%
See 2 more Smart Citations
“…119 Maximum thickness of the ligamentum flavum in the thoracic spine is at the T10-T11 level (3.3 AE 0.9 mm), possibly due to larger tensile forces and mobility at this level. 119 In the lumbar spine, ligamentum flavum thickness > 4 mm is considered hypertrophy. 102,120 The ligamentum flavum tends to be thickest at L4-L5 followed by L5-S1 and is $ 5 to 10% thicker on the left side.…”
Section: Ligamentum Flavum Thicknessmentioning
confidence: 95%
“…118 Average thickness of the ligamentum flavum in the thoracic region is 2.6 AE 0.7 mm, thinnest in the upper and thickest in the mid-to lower thoracic region. 119 No age variation was apparent. 119 Maximum thickness of the ligamentum flavum in the thoracic spine is at the T10-T11 level (3.3 AE 0.9 mm), possibly due to larger tensile forces and mobility at this level.…”
Section: Ligamentum Flavum Thicknessmentioning
confidence: 97%
See 1 more Smart Citation
“…15 Chelladurai et al reported that there was no significant difference in LFH between the two sides and sex. 16 Currently, there are two treatment approaches in patients with thickening of the LF: operative treatment and nonoperative treatment. For operative treatment, several methods of excision of the LF, eg, decompressive laminectomy and minimally invasive decompression, are performed under general principles of full decompression and spinal stability.…”
Section: Literature Reviewmentioning
confidence: 99%